Blockchain as a decentralized communication tool for sustainable development - Baker El-Ebiary Y.A.; Hatamleh A.; Aseh K.; Altrad A.; Amayreh K.T.; Hilles S.; Mohamed R.R.; Ravindran Pathmanathan P.; Aledinat L.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Planning; Sustainable development; Ubiquitous computing; Communication tools; Decentralized communications; Digital economy; Digital technologies; Global communication; Growing demand; Blockchain